2010
DOI: 10.1590/s1413-70542010000100015
|View full text |Cite
|
Sign up to set email alerts
|

Testes de vigor para avaliação do potencial fisiológico de sementes de mamona (Ricinus communis L.)

Abstract: RESUMOA qualidade de sementes de mamona tem sido avaliada rotineiramente pelo teste de germinação, cujos resultados, muitas vezes, não são confirmados em campo. Nesse contexto, os testes de vigor são essenciais, pois retratam o comportamento das sementes sob maior amplitude de ambiente. Neste trabalho, objetivou-se avaliar a eficiência de métodos para determinar o potencial fisiológico de sementes de mamona. Para tanto, foram utilizados sete lotes de sementes de mamona, cultivar AL-Guarany, apresentando teor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
1
7
0
6
Order By: Relevance
“…This indicates that from a certain amount of exposure to aging treatment the seeds lose vigor, become more sensitive to stress during germination and subsequently are unable to promote the damages reparation, losing the ability to germinate (Rajjou and Debeaujon, 2008;Samarah and Al-Kofahi, 2008). In studies carried out by Bittencourt and Vieira (2006) and Mendes et al (2010), maize (Zea mays L.) and castor (Ricinus communis L.) seeds germination reduction was observed after accelerated aging, with increasing temperature decay from 42 to 45 °C, in the first case, and from 41 to 45 °C, in the second one. The test completion on Jatropha curcas (common names include Barbados nut, purging nut, physic nut, or JCL (abbreviation of Jatropha curcas Linnaeus)) seeds by Pereira et al (2012) has provided layering of the lots only at the temperature of 41 °C, being considered limiting the temperatures of 42 and 45 °C, while for wheat (Triticum aestivum L.) seeds the temperature of 45 °C was lethal (Maia et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that from a certain amount of exposure to aging treatment the seeds lose vigor, become more sensitive to stress during germination and subsequently are unable to promote the damages reparation, losing the ability to germinate (Rajjou and Debeaujon, 2008;Samarah and Al-Kofahi, 2008). In studies carried out by Bittencourt and Vieira (2006) and Mendes et al (2010), maize (Zea mays L.) and castor (Ricinus communis L.) seeds germination reduction was observed after accelerated aging, with increasing temperature decay from 42 to 45 °C, in the first case, and from 41 to 45 °C, in the second one. The test completion on Jatropha curcas (common names include Barbados nut, purging nut, physic nut, or JCL (abbreviation of Jatropha curcas Linnaeus)) seeds by Pereira et al (2012) has provided layering of the lots only at the temperature of 41 °C, being considered limiting the temperatures of 42 and 45 °C, while for wheat (Triticum aestivum L.) seeds the temperature of 45 °C was lethal (Maia et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…With this procedure, there is reduction of the medium relative humidity, ensuring that the effects of decay should be due to temperature and exposure period (Moncaleano-Escandon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Quando as sementes foram envelhecidas a 41 ºC/72h, o lote 1 apresentou desempenho superior, sementes dos lotes 4 e 5 apresentaram resultados intermediários, e os lotes 2 e 3 apresentaram sementes de pior qualidade. Mendes et al (2010) Conforme Mendes et al (2010), as temperaturas de 41 ou 42 ºC, por períodos de tempo variando entre 48 e 72 horas são as condições mais indicadas para a condução do teste de envelhecimento acelerado, para diversas espécies.…”
Section: Resultsunclassified
“…This temperature was also the most restrictive for H. undatus seeds as inferred from to the SGI and MGT variables (Figures 2 and 3). Similarly, Mendes et al (2010) observed that temperature of 45 °C and the periods of 48, 72, and 96 h were damaging to the Ricinus communis L. seeds, accelerating their deterioration. According to Marcos Filho (1999), the increase in temperature is one of the factors contributing to accelerated seed deterioration, according to the basic principles of the accelerated aging test.…”
mentioning
confidence: 86%